2021
DOI: 10.1016/j.clnesp.2021.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Diet quality at age 5–6 and cardiovascular outcomes in preadolescents

Abstract: Background & aims: Specific dietary components during childhood may affect risk factors for cardiovascular disease. Whether overall higher diet quality prevents children from adverse cardiovascular outcomes remains contradictive. We aimed to examine the associations between diet quality at age 5e6 years and cardiovascular outcomes after a 6-year follow-up. Methods: We used data from the Amsterdam Born Children and their Development study, a multi-ethnic birth cohort. Dietary intake was assessed at age 5e6 usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…These findings provide an important contribution to the current evidence on childhood diet quality and BP, which is based on a limited number of cross-sectional [6,13,14] and longitudinal studies [16][17][18]. In line with our findings, few previous studies have observed higher BP among children consuming generally less healthy diets.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings provide an important contribution to the current evidence on childhood diet quality and BP, which is based on a limited number of cross-sectional [6,13,14] and longitudinal studies [16][17][18]. In line with our findings, few previous studies have observed higher BP among children consuming generally less healthy diets.…”
Section: Discussionsupporting
confidence: 90%
“…Since the 2018 systematic review [ 6 ], few additional cross-sectional studies have been published showing slightly lower diastolic blood pressure (DBP) [ 13 ] or systolic blood pressure (SBP) [ 14 ] among children consuming healthier dietary patterns, or no association between dietary patterns and BP [ 15 ]. Two longitudinal studies from the Netherlands found higher diet quality in early childhood (age 5 to 8) was associated with lower DBP and SBP between age 10 and 12, however, these studies have not accounted for changes in diet quality during follow-up [ 16 , 17 ]. We are aware of one cohort study which used longitudinal diet data from children recruited through the Longitudinal Study of Australian Children (LSAC) who also participated in the Child Health CheckPoint at age 10/11 when detailed cardio-metabolic phenotypic outcomes were measured [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a healthier diet was associated with lower mortality [ 4 ], better cardiovascular health [ 5 ], and lower risk of metabolic syndrome [ 6 ], type 2 diabetes [ 7 ], hypertension [ 8 ] or IR in adults [ 9 , 10 ]. Moreover, there are some studies in children that have observed that a higher adherence to a healthy dietary pattern was associated with better cardiovascular health [ 11 ] and lower risk of metabolic syndrome [ 12 , 13 ], hypertension [ 14 ], or IR [ 15 , 16 ], although in children, the evidence is still very scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Poor diet quality is associated with metabolic disturbances, including increased body fat content, dyslipidemia, higher blood pressure and metabolic syndrome in adults [ 1 ] and children [ 2 , 3 ]. Moreover, a diet abundant with unhealthy choices, such as a high consumption of sugar-sweetened beverages and a low consumption of fruits and vegetables, has been linked to an increased risk of cardiometabolic diseases in adults [ 4 ].…”
Section: Introductionmentioning
confidence: 99%